2021
DOI: 10.1016/j.scitotenv.2021.148167
|View full text |Cite
|
Sign up to set email alerts
|

Temporal transition of racial/ethnic disparities in COVID-19 outcomes in 3108 counties of the United States: Three phases from January to December 2020

Abstract: Early studies reported higher risk of COVID-19 outcomes for racial/ethnic minorities in the early phase of the pandemic in the United States. While the initial surge of COVID-19 was concentrated in some areas, COVID-19 became pervasive across the entire continent with high impacts in the northern region and central region in the end of 2020. With this geographical transition, we aim to investigate patterns of these racial/ethnic disparities over time. We assessed associations of percentage of race/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
(28 reference statements)
2
10
0
1
Order By: Relevance
“…The highest number of papers that included population density in their analysis is on the county scale (as shown in Table 1 ). About 63 % of documents on this scale found population density as a driving force of COVID-19 spread ( Wong and Li, 2020 ; Kim et al, 2021 ; Aw et al, 2021 ; Jo et al, 2021 ; Qeadan et al, 2021 ; Q. Li et al, 2021 ; Lee et al, 2021 ). It is worth mentioning that 17 out of 27 of these papers were conducted in the US.…”
Section: Resultsmentioning
confidence: 99%
“…The highest number of papers that included population density in their analysis is on the county scale (as shown in Table 1 ). About 63 % of documents on this scale found population density as a driving force of COVID-19 spread ( Wong and Li, 2020 ; Kim et al, 2021 ; Aw et al, 2021 ; Jo et al, 2021 ; Qeadan et al, 2021 ; Q. Li et al, 2021 ; Lee et al, 2021 ). It is worth mentioning that 17 out of 27 of these papers were conducted in the US.…”
Section: Resultsmentioning
confidence: 99%
“…Em diversos países do mundo, sobretudo nos Estados Unidos, autores têm relatado disparidades étnico-raciais sobre desfechos relacionados à COVID-19. Wong et al (2021) reportaram maiores taxas de infecção e mortalidade em populações negras, hispânicas, havaianas nativas e asiáticas, enquanto o estudo conduzido por Kim et al (2021), em 3108 condados norte-americanos, apontou maiores taxas de casos e mortalidade entre negros e hispânicos, mas relatam que estas taxas foram flutuantes ao longo do tempo, decorrentes de influências sociais, culturais e políticas.…”
Section: Discussionunclassified
“…Our paper identified how the determinants of COVID-19 transmission varied during the three pandemic waves, further implying the necessity of unraveling the complexity of the pandemic across time. While a couple of recent papers were able to address the discrepancies among the waves ( Gaisie et al, 2022 ; Kim, Zanobetti, and Bell, 2021 ), our paper is the first to provide a holistic view based on the COVID-19 cases in the United States. In this section, we mainly address the changes in the effects of related factors across the three pandemic waves focusing on our four hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“…First, most studies focus on the early stage of the pandemic while assuming that the relationship between either population or built environment related factors and COVID-19 transmission would be consistent. We have recently witnessed a couple of case studies which reported that the relationship could differ across waves, implying the necessity of further investigation ( Kim, Zanobetti, & Bell, 2021 ; Gaisie et al, 2022 ). To the best of our knowledge, however, there is yet no literature on how the relationship between built environment and COVID-19 transmission differ by pandemic waves in the United States.…”
Section: Literature Reviewmentioning
confidence: 99%